2022
DOI: 10.1055/s-0041-1731674
|View full text |Cite
|
Sign up to set email alerts
|

Artroplastia reversa de ombro: Avaliação dos resultados clínicos e funcionais de acordo com a etiologia

Abstract: Resumo Objetivo Avaliar os resultados clínicos da artroplastia reversa do ombro no tratamento de suas diversas indicações. Métodos Estudo longitudinal retrospectivo que analisou os resultados dos escores Constant, UCLA e amplitudes de movimentos dos pacientes submetidos à artroplastia reversa do ombro. Resultados Foram analisados 28 pacientes, a média de idade foi de 75.6 anos, com seguimento médio de 45 meses. No geral, obtivemos uma variação significativa (p < 0,0001) entre o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A report from an orthopaedic service in Brasília, Brazil, detailed the performance of RSA in 35 patients from 2011 to 2016. However, the data revealed information of 28 individuals, with only 11 patients where the indication for the RSA procedure was RCA [ 21 ]. Although living in the same country, inequalities exist in Brazil, which can be illustrated by a mean GDP/capita below US$ 4700.00 in our region as compared to over US$ 16,500.00 mean GDP/capita in Brasilia, Brazil [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A report from an orthopaedic service in Brasília, Brazil, detailed the performance of RSA in 35 patients from 2011 to 2016. However, the data revealed information of 28 individuals, with only 11 patients where the indication for the RSA procedure was RCA [ 21 ]. Although living in the same country, inequalities exist in Brazil, which can be illustrated by a mean GDP/capita below US$ 4700.00 in our region as compared to over US$ 16,500.00 mean GDP/capita in Brasilia, Brazil [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has evaluated the clinical outcomes after rTSA for various surgical indications. 22 , 23 , 25 Chelli et al 25 conducted a retrospective study and evaluated various survivorship analyses stratified by primary rTSA versus revision rTSA, age (<60 years, 60 to 69 years, 70 to 79 years, ≥80 years), and sex. Our study found prosthetic survivorship of 90.5% in the PHF group and 85.2% in the RTCA group at the 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[19][20][21] While many studies have reported outcomes after rTSA compared with another surgical management option to treat the same pathology, there are limited studies that conduct a granular comparison of rTSA performed for PHF versus RTCA. 22,23 Therefore, the purpose of this study was to report and assess shortterm survivorship of rTSA performed for PHFs and RTCA and secondarily to evaluate whether PHF patients can achieve similar functional outcomes and end range of motion (ROM) compared with RTCA patients.…”
mentioning
confidence: 99%
“…At the same time, due to the magnifying effect of arthroscopy, delicate operations can be performed under the microscope, reducing the damage to the unnecessary surrounding tissues. [10] Blood loss is an essential factor that can significantly impact the prognosis of rotator cuff injury. [11] Bleeding can occur in the joint cavity and the soft tissue of the joint cavity, which can cause synovitis, scarring, secondary joint fibrosis, and soft tissue swelling.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, due to the magnifying effect of arthroscopy, delicate operations can be performed under the microscope, reducing the damage to the unnecessary surrounding tissues. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%